Генетичний поліморфізм ІЛ-10 rs 1800896 та його вплив на рівень ІЛ-10 в сироватці крові у взаємозв`язку із тяжкістю перебігу оперізувального герпесу у дорослих хворих - Оніщенко, Неллі Вадимівна; Onishchenko, N. V. (My University, 2019)
Resume. The article reveals the study of IL-10 genetic polymorphism (rs 1800896) in patients with herpes zoster and its effect on serum cytokine concentration. It is shown that the polymorphism of IL-10 gene influences on severity of herpes zoster, development of complications and localization of defeat, and influence on the IL-10 level in serum of patients with herpes zoster. Мета. Визначити роль генетичного поліморфізму ІЛ-10 (rs 1800896) в перебігу оперізувального герпесу у дорослих у взаємозв’язку із рівнем цього цитокіну в сироватці крові.
Genetic polymorphism IL-10 rs 1800896 and its influence on il-10 level in blood serum in associacion with severe course of herpes zoster in adults patients
Keywords: тези доповідей